A rare case of total hip replacement in an 11-year-old female: rehabilitation goals and challenges - a case report - Paranjape, Swati S.; Lokwani, Muskaan D.; Keswani, Pranav P.; Mohanty, Shubhranshu S. (International Journal of Contemporary Pediatrics, 2024)
This case report describes a unique pediatric patient, the first and youngest in India, who underwent total hip replacement (THR) for right ankylosed hip. Patient presented with preoperative musculoskeletal deformities, posing challenges for postoperative rehabilitation. This 11-year-old female presented with non-traumatic insidious right hip pain, limping, right hip flexion and abduction deformity. Patient was diagnosed with idiopathic chondrolysis of the hip through exclusion and clinico-radiological findings. Patient underwent surgery for ceramic-on-ceramic THR. Fusion of triradiate cartilage and epiphysis and Risser’s skeletal maturity staging were confirmed. Postoperative examination revealed right hip flexion and abduction deformity resulting in pelvic obliquity, which led to limb length discrepancy and functional scoliosis. There was increased anterior pelvic tilt, altering the gait pattern. Adhering to THR restrictions, rehabilitation strategies were tailored to restore normal pelvic orientation and address deformities through manual stretching of right hip abductor, tensor fascia latae, iliopsoas and rectus femoris. A left-sided shoe raise was also given. Lumbar segmental muscle activation, pelvic floor muscle training and gait training were crucial parts of the rehabilitation protocol. At ten-week, prodigious outcomes were achieved in the form of complete pain relief, complete correction of abduction and flexion deformity, normal pelvic alignment in the frontal plane and independent, stable full weight-bearing ambulation after two years of disabling ordeal suffering. However, minimal compensation of the anterior pelvic tilt persisted. Rehabilitation of this challenging patient with multiple deformities achieved excellent outcomes at ten-week post-rehabilitation. Thus, a tailored meticulous rehabilitation program can significantly improve quality of life.